IMPULSE OSCILLOMETRY FOR DIAGNOSIS OF EARLY CHANGES IN THE RESPIRATORY SYSTEM FUNCTIONAL STATE IN PATIENTS WITH MILD ASTHMA - N. M. Leontieva; I. V. Demko; E. A. Sobko; O. P. Ishchenko; I. A. Solov'yova (SINAPS LLC, 2019)
Currently, the analysis of respiratory function of lungs at suspicion of obstructive pulmonary diseases is recommended to start with spirometry as the most sensitive method of obstruction detection. However, data on informative value and specificity of a method are contradictory. To obtain reliable results good cooperation of the patient and health professionals is necessary. Impulse oscillometry is a noninvasive method of general respiratory resistance assessment, which does not require forced exhalations. The sensitivity and specificity of this method remain undecided as well as the obtained parameter interpretation. The objective of this work was to study opportunities of impulse oscillometry in diagnostics of early respiratory dysfunctions of ist most informative indicators correlating with parameters of spirometry and body plethysmography.Materials and methods. Patients with the established diagnosis of mild asthma (n=68) were examined. In 71% of patients, obstructive respiratory dysfunction was revealed. In the control group (n=41) there were no abnormalities.Results. In most of patients with revealed via spirometry and body plethysmography obstructive disturbances the increase in indicators of absolute frequency dependence of the resistive component of the respiratory impedance at the oscillation frequency of 5 and 20 Hz (Rrs5-Rrs20) and the reactance area (AX). Increase in Rrs5-Rrs20 was revealed in 48 (71%) patients and the increase in AX was observed in 44 (65%) of the surveyed, patients with 42 (61%) patients without the increase of reactance (Xrs5) and resistance (Rrs5).Conclusion. The absolute frequency dependence of Rrs5-Rrs20 and AX are the most informative parameters of impulse oscillometry. In some patients the IOM findings were more significant in comparison with spirometry ones.